Dropout in clinical trials of pharmacological treatment for methamphetamine dependence: the role of initial abstinence. (16th February 2017) - Cook, Ryan; Quinn, Brendan; Heinzerling, Keith; Shoptaw, Steve
Abstract: Background and Aims: High rates of loss to follow‐up represent a significant challenge to clinical trials of pharmacological treatments for methamphetamine (MA) use disorder. We aimed to estimate and test the relationship between achieving and maintaining abstinence in the initial weeks of study participation and subsequent retention in such trials, hypothesizing that participants able to achieve early abstinence would be less likely to drop out. Design: Data from four randomized controlled trials (RCTs) of pharmacological treatments for MA use disorder were pooled and analyzed using a random‐effects approach. Setting: All trials were conducted in the greater Los Angeles, CA, USA area. Participants: A total of 440 participants were included; trials were conducted between 2004 and 2014. Measurements: Participants' ability to achieve a brief period of initial abstinence was measured as the number of MA‐negative urine screens completed in the first 2 weeks of the trials. Outcomes were the likelihood of dropout, i.e. missing two consecutive weeks of scheduled urine drug screens, and the number of days participants were retained in the trials. Findings: Study participants achieved an average of three (of six possible) negative urine screens during the first 2 weeks of the trials, 51% dropped out and the average number of days retained was 60 (of 90 maximum). Each additional negative urine screen achieved during the first 2 weeks of the study reduced multiplicatively the odds of dropout by 41% [odds ratio (OR) = 0.59, 95% confidence interval (CI) = 0.53, 0.66]. Abstinence was also a significant predictor of retention time; the hazard ratio for non‐completion was 0.75 per additional negative urine screen (95% CI = 0.71, 0.80). Conclusions: Participants in randomized controlled trials of pharmacological treatments for methamphetamine use disorder who are able to achieve a brief period of early abstinence are retained longer in the trials and are less likely to drop out overall.